An exploration of the introduction of Communities of Practice from a change management perspective - Strattner, Jana Marina (2016)
This thesis presents the results of an exploration of the introduction of Communities of Practice (CoPs) from a change management perspective within a construction company in the UK. Due to a lack of research on CoPs in terms of change management, the research contributes to the existing academic literature in several ways. Firstly, it illustrates how successful CoPs substantially support change management capabilities by increasing knowledge sharing and organisational learning. Secondly, due to the introduction of CoPs being seen as change in itself, the research discovers factors that are important in terms of successful change management. Particularly employee empowerment, communication and long- term planning are identified, which corroborates the current developments in the change management literature. Thirdly, the research reinforces findings of previous literature on CoPs that supportive leadership, a company culture - which is characterised by high levels of trust and collaboration, individual motivation to share knowledge and user- friendly technology are all considered important factors in terms of a CoPs success. Lastly, combining those findings, the research contributes to the literature by presenting practical recommendations for the successful implementation of CoPs. Particularly distributing more responsibilities to employees by using a middle-out approach, adjusting reward structures and giving sufficient importance to CoPs as a tool for enhancing knowledge sharing, should be considered in order to ensure the successful introduction of CoPs.